2022
DOI: 10.1155/2022/3876240
|View full text |Cite
|
Sign up to set email alerts
|

General Use of Chinese Herbal Products among Female Patients with Mastitis in Taiwan

Abstract: Objectives. Little information is available regarding the use of Chinese herbal medicine to treat mastitis. This study evaluated the prescription patterns of Chinese herbal medicine products in women with mastitis in Taiwan. Design. This is a population-based cross-sectional study. Setting. 8,531 women aged 20–49 years, who received a diagnosis of mastitis between 2004 and 2013, were identified from the Longitudinal Health Insurance Database in Taiwan. We collected data on demographic characteristics, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…These herbs have been commonly prescribed to support lactation in TCM. Wang Bu Liu Xing is traditionally used for promoting lactation and treating breast abscess (45), while Lu Lu Tong has been linked with improving circulation and reducing swelling (46). Our study further revealed that among dual combinations of CHP, the pairing of Wang Bu Liu Xing and Lu Lu Tong was the most common.…”
Section: Discussionmentioning
confidence: 51%
“…These herbs have been commonly prescribed to support lactation in TCM. Wang Bu Liu Xing is traditionally used for promoting lactation and treating breast abscess (45), while Lu Lu Tong has been linked with improving circulation and reducing swelling (46). Our study further revealed that among dual combinations of CHP, the pairing of Wang Bu Liu Xing and Lu Lu Tong was the most common.…”
Section: Discussionmentioning
confidence: 51%